Perkembangan MUI Kota Bandung tahun 1975-1978 - Abdullah, Luqman; Permana, Agus; Fajriudin, Fajriudin (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research aims to examine how the development of MUI Bandung City during the leadership of Ahmad Naswari Mansur or more specifically in 1975-1978. Of course, the development of MUI Bandung City cannot be separated from how MUI was initially formed, how the social religious condition in Bandung city at that time, and also how the background of the formation of MUI Bandung City. This research uses historical research method whose stages consist of Heuristic, Criticism, Interpretation, and Historiography. This research results in information that MUI Bandung City was born not long after the central MUI was established and its first chairman came from the military of Kodam III Siliwangi, Ahmad Naswari Mansur, and how the work program implemented by MUI Bandung City during the leadership of Ahmad Naswari Mansur.